C23 gene regulates the nucleolin structure and biosynthesis of ribosomes in bovine intraspecific and interspecific somatic cell nuclear transfer embryos. Issue 11 (20th October 2021) - Su, Guanghua; Wang, Lina; Gao, Guangqi; Wu, Shanshan; Yang, Lei; Wu, Meiling; Liu, Xuefei; Yang, Miaomiao; Wei, Zhuying; Bai, Chunling; Li, Guangpeng
Abstract: Somatic cell nuclear transfer (SCNT) can reprogram differentiated somatic cells to produce individual animals, thus having advantages in animal breeding and chromatin reprogramming. Interspecies SCNT (iSCNT) provides extreme cases of reprogramming failure that can be used to understand the basic biological mechanism of genome reprogramming. It is important to understand the possible mechanisms for the failure of zygotic genome activation (ZGA) in iSCNT embryos in order to improve the efficiency of SCNT embryos. In the present study, we compared the development of bovine‐bovine (B‐B), ovine‐ovine (O‐O) SCNT, and ovine‐bovine (O‐B) iSCNT embryos and found that a developmental block existed in the 8‐cell stage in O‐B iSCNT embryos. RNA sequencing and q‐PCR analysis revealed that the large ribosomal subunit genes (RPL) or the small ribosomal subunit genes (RPS) were expressed at lower levels in the O‐B iSCNT embryos. The nucleolin (C23) gene that regulates the ribosomal subunit generation was transcribed at a lower level during embryonic development in O‐B iSCNT embryos. In addition, the nucleolin exhibited a clear circular‐ring structure in B‐B 8‐cell stage embryos, whereas this was shell‐like or dot‐like in the O‐B embryos. Furthermore, overexpression of C23 could increase the blastocyst rate of both SCNT and iSCNT embryos and partly rectify the ring‐like nucleolin structure and the expression of ribosomal subunit related genes were upregulation, while knockdown of C23 increased the shell‐like nucleolin‐structure in B‐B cloned embryos and downregulated the expression of ribosomal subunit related genes. These results implied that abnormal C23 and ribosome subunit gene expression would lead to the developmental block of iSCNT embryos and ZGA failure. Overexpression of the C23 gene could partly improve the blastocyst development and facilitate the nucleolin structure in bovine preimplantation SCNT embryos.